Determining The Magnitude Of Land Size Adjustment In Real Property Valuation - Djoko Setijono Ko (Jurnal Manajemen Aset dan Penilai, 2022)
This paper presents the development of a quantitative technique to determine the magnitude of land size adjustment, based on the ratio between cumulative paired difference of land price indication (CPDP) and cumulative paired difference of land size (CPDS). The proposed technique was then empirically tested to evaluate land size adjustment of market comparison data for the purpose of valuing a real property on Jalan Otto Iskandardinata in East Jakarta. The results of empirical test suggest that the magnitude of adjustment produced using Relative Paired Difference (RPD) based technique are coherent with subjective-based adjustment, yet is able to reveal the inconsistency of subjective adjustment. Therefore, the developed technique presented in this paper is more advantageous than subjective-based adjustment in terms of improving proportionality and reducing inconsistency when determining the magnitude of land size adjustment.